Aquatic training with special equipment to improve health-related fitness - guelatti, yazid (sports creativity, 2025)
This topic examines (aquatic training with special equipment to improve health-related physical fitness). To shed light on this topic, we posed the following questions in advance: What is the impact of a proposed aquatic training program using assistive devices on health-related physical fitness? - Can health-related fitness be improved by using the aquatic environment? - Does the use of assistive devices play an effective and positive role in improving health-related physical fitness in an aquatic environment? The following conclusions were reached: There was a noticeable but not statistically significant improvement in body mass, body mass index, resting metabolic rate, muscle mass, and water mass. - The experimental group outperformed the control group in post-measurements of BMI, fat percentage, and all health-related physical fitness components. It was found that the proposed aquatic program had a very clear effect on flexibility.